Compositional features of the extracts from the methanolysis of Xilingol No. 6 lignite. (15th June 2019) - Li, Sheng; Zong, Zhi-Min; Wang, Sheng-Kang; Xu, Mei-Ling; Wei, Xian-Yong; Liu, Fang-Jing
Highlights: About 34.4% organic matter in XL was converted into soluble species via methanolysis. The cleavage of >C-O- bond produces more phenolic compounds. Most of the N x O y class species contain imidazole or pyridine ring substituted by furan ring, methoxy and/or ester group. Abstract: Xilingol No. 6 lignite (XL) was subjected to thermal dissolution in methanol at 200 °C, 240 °C, 280 °C, and 320 °C, respectively. Each reaction mixture was sequentially extracted with methanol and isometric carbon disulfide/acetone mixed solvent in a modified Soxhlet extractor to afford extracts a and b, respectively. According to the analysis with a Curie-point pyrolyzer-gas chromatograph/mass spectrometer, the main products from the flash pyrolysis of Ea320, i.e., Ea obtained from XL methanolysis at 320 °C, are phenolic compounds. The analysis with a quadrupole-orbitrap mass spectrometer indicates that N 3 O 2 - N 3 O 4 are predominant nitrogen- and oxygen-containing class species (NOCCSs) in Ea320 . In the NOCCSs, nitrogen atoms mainly exist in the forms of pyridine, imidazole or pyrazole, and pyrazine or pyrimidine, while the main oxygen atoms exist in alkoxy, furan, ester or carbonyl group. In addition, possible pathways for the formation of the NOCCSs were speculated.